Analysis of multi-factor dynamic coupling and government intervention level for urbanization in China: Evidence from the Yangtze River economic belt - Wenchao Bao; Beier Chen; Minghui Yan (Economics: The Open-Access, Open-Assessment Journal, 2024)
Effective coordination of urbanization dynamics and influencing factors is crucial for achieving balanced development. This study analyzes urbanization, economic, and environmental data of the Yangtze River Economic Belt from 2005 to 2019 using the Coupling Degree model and Entropy Method with the Analytic Hierarchy Process, focusing on the coordination between urbanization development, economic development, and environmental protection (EP). It highlights the significance of government interventions and the necessary level of government engagement in environmental matters for harmonized development across regions. Findings show that higher urbanization and economic levels align with robust environmental safeguards facilitated by active government interventions. Conversely, lower levels may lead to reduced EP, influenced by government actions. The study enhances understanding of the interplay between urbanization, economic growth, and environmental conservation, underlining the government's role in coordination. Different development stages reveal the importance of government environmental interventions for policy formulation. Introducing the relatively unexplored variable of government policy, the study establishes a comprehensive framework for interventions, enriching coordination analysis and insights.
Keywords: 330; urbanization; economic development; coupling degree; environment; government policy; the Yangtze River Economic Belt